Buying attitude in social networks of the Z generation of Lima Sur - García-Salirrosas, Elizabeth Emperatriz (2020)
Objective. Knowing the buying attitude through social networks of generation Z. Method. Under the quantitative approach, a sample of 401 young people from the south of Lima responded to a survey on the use they make of social networks and their buying attitude through them, for this a statistical analysis of the trend measures was applied. central such as the mean, median, and mode. Results. The analysis of the data positions WhatsApp as the application that leads in use with 41% followed by Facebook with 28%. 80% of this generation enter their social networks through the use of a mobile phone or smartphone, only 11.7% use a laptop. 30.2% stay on social media for 2 to 4 hours and 26% for 6 to 8 hours. However, 51.1% of generation Z are occasionally influenced by this social network when making their purchases. Conclusion. Generation Z is the sector where there is a massive use of social networks, however, these networks do not significantly influence their purchasing behavior.